Diseño e implementación de un sistema integral de gestión de seguridad y manejo de desechos en el LabCIVCO - Serrano-Chavarría, Esteban (Instituto Tecnológico de Costa Rica, 2010)
The present project arises as a need of the materials laboratory of the Costa Rican Building Research Center (LabCIVCO), which have had initiated the process of accreditation. One of the important points for the accreditation that the Costa Rican Accreditation Entity, ECA demands in the norm INTE: ISO/IEC 17025:2005, indicates the relevancy of the good professional practices application in all the processes. Therefore, there was generated an Emergency Plan, which includes the facilities and personnel of the LabCIVCO. This documentation will use as instrument to face emergency situations; also there was generated a Plan of Waste Management, which is part of the quality policies and environmental management of the LabCIVCO, to give a suitable managing to the generated waste. For the success of these Plans, the emergency signposting and occupational safety was necessary in the facilities, including first aids and fire extinction equipment. Additional trainings were offered to the personnel, in order that they have basic knowledge of every topic of the project. The document endorses the policies of quality, the commitment in safety and environment policies of the laboratory. The procedures used were: INTECO, NTP and NFPA, guides of the Department of Health, INS manuals and diverse professional consults.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Señalización; NTP; NFPA; INS; INTECO; Plan de emergencias